559 Fostriecin potentiates genome instability and anti-tumor immunity in ovarian cancer. (10th December 2020) - Raja, Remya; Wu, Christopher; Butler, Kristina; Curtis, Marion
Abstract : Background: Increased immune infiltration in ovarian tumors has been linked to improved patient outcome. Nonetheless, responses to checkpoint blockade therapies have been disappointing in ovarian cancer patients. This has been attributed to the low mutational burden present in ovarian tumors. However, many tumor antigens have been identified in ovarian cancer, which underscores the critical need to identify new treatment strategies that will trigger anti-tumor immunity in ovarian cancer. Recent studies have revealed that defects in DNA damage repair (DDR) pathways can contribute to improved responses to immune-directed therapies. 1 2 We previously discovered that CT45 expression sensitizes ovarian cancer cells to chemotherapy via its interaction with the protein phosphatase 4 (PP4) complex. 3 PP4 is known to play a key role in DDR pathways; however, its potential effects on anti-tumor immunity remain unknown. Methods: Using fostriecin, a commercially available inhibitor of PP4, we studied the effect of fostriecin on chemosensitivity using cell cycle analysis and cell viability assays. To study the effect of fostriecin on DNA damage, we performed comet assays and measured micronuclei along with FANCD2 foci formation. Furthermore, using western blot, qPCR, and T cell activation assays, we assessed the role of fostriecin in promoting an inflammatory response. We tested the efficacy of combining fostriecin with carboplatin and PD-1 inhibition in a syngeneic mouse model of ovarian cancer. Results: Our results show that fostriecin treatment combined with carboplatin leads to increased carboplatin sensitivity, DNA damage, and micronuclei formation. Using a panel of ovarian cancer cells, we show that fostriecin treatment triggers an anti-tumor immune response via STAT1 activation resulting in increased expression of pro-inflammatory cytokines. Furthermore, in a syngeneic mouse ID8 ovarian cancer cell line, we demonstrate that combination treatment of fostriecin and carboplatin significantly increased CD8 T cell activation over carboplatin treatment alone. Conclusions: Our work has identified a role for PP4 inhibition in promoting anti-tumor immunity. These findings form the groundwork for the rationale design of a clinical trial combining PP4 inhibitors with chemo-immunotherapy as a new approach in ovarian cancer treatment. References: Rodier F, Coppé J-P, Patil CK, Hoeijmakers WAM, Muñoz DP, Raza SR, et al. Persistent DNA damage signalling triggers senescence-associated inflammatory cytokine secretion. Nature Cell Biology 2009; 11: 973–979. Zhang H, Christensen CL, Dries R, Oser MG, Deng J, Diskin B, et al. CDK7 Inhibition potentiates genome instability triggering anti-tumor immunity in small cell lung cancer. Cancer cell 2020;37 :37–54.e39. Coscia F, Lengyel E, Duraiswamy J, Ashcroft B, Bassani-Sternberg M, Wierer M, et al. Multi-level proteomics identifies CT45 as a chemosensitivity mediator and immunotherapy target in ovarian cancer. Cell 2018;175 :159–170.e116.